Produtividade, qualidade química e sensorial da ora-pro-nóbis fertilizada com adubo orgânico e mineral - Barbosa, Gisiliana de Oliveira (Universidade Federal de São Carlos, 2021)
The search for barbados gooseberry (Pereskia aculeata Mill.) has encouraged its cultivation on a bigger scale. However, the species’ demand for nutrients and response to fertilization is not yet established. The aim of this study was to evaluate the effects of fertilization in agronomical, chemical and sensorial characteristics of Barbados gooseberry in a narrow row spacing and successive crops. The individuals have been cultivated without fertilization, and also with mineral and organic fertilizers, in a randomized block design with 7 replicates. Production analyses were carried out at 210, 270 and 330 days after transplanting (DAT), whereas mineral and protein contents were measured at 210 and 330 DAT and sensory analysis happened at 330 DAT. The mineral fertilization was more efficient to supply nutrients (P,K) and increase productivity.Fertilizers didn’t differ on their leaf protein content, chlorophyll concentrations and sensory characteristics.
Productivity, chemical and sensorial quality of barbados gooseberry fertilized with organic and mineral fertilizer
Keywords: Pereskia aculeata Miller; Análise de crescimento; PANC; Nutrição mineral; Proteína; Sensorial; Growth analysis; UFP (Unconventional Food Plant); Mineral nutrition; Protein; Sensory; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS